Mathematics Teaching Tools for Implementing the Independent Curriculum Stage B Class 4 - Putra, I Gede Diyana; I Wayan Suastra; I Made Gunamantha (Universitas Pendidikan Ganesha, 2024)
The Merdeka Curriculum has been prepared to be fully implemented in 2024. These changes often affect the learning instruments used in class. In facing these changes, schools need to develop additional learning tools in implementing the Independent Curriculum. The aim of this research is to provide a more comprehensive, in-depth and contextual learning experience for students in understanding basic mathematical concepts. This research is development research that develops mathematics learning instruments for fourth grade students in implementing the Merdeka Curriculum. The population of this research was 168 students. Randomly, the experimental group only consisted of 30 students, while the students selected as the control group were 26 students. This product was developed using the Plomp development model which consists of 5 stages; initial observation, preparation of product design, product realization, testing, evaluation and revision, and implementation. The research instruments used in this research were observation sheets, questionnaires, pretest and posttest, and interview guidelines. The final product contains learning objectives, learning modules, and assessment instruments. The data analysis techniques used in this research are normality test, homogeneity test, t test, and n-gain score. The n-gain results show the product is in the medium category. The results of the t-test showed an increase which showed an increase from the pre-test to post-test scores. This means there is change. that valid, practical and effective learning instruments can be developed in improving students' cognitive learning outcomes. Implications of this research can be used to solve practical problems, improve existing systems, or develop new theories.